Physicochemical properties and microstructure of corn flour–cellulose fiber extrudates. Issue 5 (16th March 2021) - Zhao, Yilin; Zhao, Chengbin; Tang, Xudong; Zhou, Jingyi; Li, Hao; Zhang, Hao; Liu, Jingsheng
Abstract: In this study, corn flour with 24% w/w moisture content was extruded, and cellulose at varied weight ratios was added in order to investigate its effect on the extrudate's physicochemical properties. Twin‐screw extrusion was divided into five temperature zones, and the screw temperature profile was 60℃, 120℃, 140℃, 120℃, and 110℃, respectively, and screw speed was 150 rpm. The cellulose content was 1%–15% w/w. Results showed that the addition of cellulose led to an increase in hardness, L * and b * of the extruded samples, and a decrease in degree of expansion, a *, thermal enthalpy of the sample paste. The sample paste exhibited a solid‐like characteristic. Microscopic morphology analysis showed that surface wrinkles of the sample increased with the increase of cellulose addition. The addition of cellulose can effectively increase the degree of puffing of corn flour–cellulose fiber extrudates. Abstract : In this study, different ratios were selected to study the effect of cellulose on corn flour extrusion processing.